Evaluation of the Position and Incidence of Impaction of Mandibular Third Molars in Different Anteroposterior and Vertical Skeletal Patterns: A Retrospective Study - Zarzora, Ahmed; Foda, Manal Yehia; El Dawlatly, Mostafa Mohamed; Dehis, Heba Mohamed (Open Access Macedonian Journal of Medical Sciences, 2022)
Aim: To evaluate the incidence of impacted mandibular third molar in different anteroposterior and vertical facial skeletal patterns and to evaluate the angle of impaction of mandibular third molar. Methodology: 207 Panoramic and lateral cephalometric radiographs for patients above 20 years old with impacted mandibular third molar were recruited from the orthodontic department clinics in multiple universities in Egypt and traced using WebCeph ™ software. From the lateral cephalograms, three anteroposterior measurements were taken which were termed as ANB, A-B difference and Wits appraisal and three vertical angles were measured which were SN/MP, MMPA and FMPA to determine different skeletal facial types. The angulation of mandibular third molar impaction was determined by β angle according to Winter’s classification from the orthopantomogram. Results: Among all 207 analyzed cases, impacted third molars were detected in (38.6%) cases unilaterally and (61.4%) bilaterally. Anteroposteriorly, the higher percentage of total impactions was found in subjects with a class 2 skeletal pattern (97.2%). Vertically, the higher percentage of total impactions was found in subjects with a mesocephalic facial pattern (45.9%). The most common type of impaction was mesioangular based on Winter’s classification. Conclusions: A higher incidence of lower third molar impaction was found in subjects with a class 2 skeletal pattern. A higher incidence of lower third molar impaction was found in subjects with a mesocephalic facial pattern. In almost all skeletal facial types, the mesioangular position of the impacted mandibular third molar was the most prevalent position.